Two independent mouse lines carrying the Nav1.7 I228M gain-of-function variant display dorsal root ganglion neuron hyperexcitability but a minimal pain phenotype. Issue 6 (June 2021) - Chen, Lubin; Wimalasena, Nivanthika K.; Shim, Jaehoon; Han, Chongyang; Lee, Seong-Il; Gonzalez-Cano, Rafael; Estacion, Mark; Faber, Catharina G.; Lauria, Giuseppe; Dib-Hajj, Sulayman D.; Woolf, Clifford J.; Waxman, Stephen G.
Abstract : Abstract: Small-fiber neuropathy (SFN), characterized by distal unmyelinated or thinly myelinated fiber loss, produces a combination of sensory dysfunction and neuropathic pain. Gain-of-function variants in the sodium channel Nav 1.7 that produce dorsal root ganglion (DRG) neuron hyperexcitability are present in 5% to 10% of patients with idiopathic painful SFN. We created 2 independent knock-in mouse lines carrying the Nav 1.7 I228M gain-of-function variant, found in idiopathic SFN. Whole-cell patch-clamp and multielectrode array recordings show that Nav 1.7 I228M knock-in DRG neurons are hyperexcitable compared with wild-type littermate-control neurons, but despite this, Nav 1.7 I228M mice do not display mechanical or thermal hyperalgesia or intraepidermal nerve fiber loss in vivo. Therefore, although these 2 Nav 1.7 I228M knock-in mouse lines recapitulate the DRG neuron hyperexcitability associated with gain-of-function mutations in Nav 1.7, they do not recapitulate the pain or neuropathy phenotypes seen in patients. We suggest that the relationship between hyperexcitability in sensory neurons and the pain experienced by these patients may be more complex than previously appreciated and highlights the challenges in modelling channelopathy pain disorders in mice. Abstract : Two independent Nav 1.7 I228M knock-in mouse lines suggest a complicated relationship between dorsal root ganglion neuron hyperexcitability and painful neuropathy, highlighting challenges in modelling channelopathic pain disorders in mice.